Barriers to the inclusion of refugee and asylum-seeking children in schools in England. Issue 5 (2nd September 2020) - McIntyre, Joanna; Hall, Christine
ABSTRACT: This article reports a study of the barriers faced by headteachers seeking to include young asylum seekers and refugees into secondary schools in England. We trace the new discourses and assemblages of authority created at city level by recent policy changes. Drawing on in-depth interviews with headteachers, we share their experiences of navigating layered ecologies of systemic challenges to their inclusive stance towards provision for newly arrived children. We argue that structural and policy moves in England towards greater emphasis on controlling (im)migration and economistic measures of educational performance, alongside centralised funding and governance and the reduction of place-based regional autonomy, have led to greater invisibility of asylum-seeking and refugee pupils and to greater vulnerability and visibility/accountability of school leaders. These changes have had an adverse impact on inclusion in English schools and cities.